A Systematic Review of Associations between Amount of Meditation Practice and Outcomes in Interventions Using the Four Immeasurables Meditations - Zeng, Xianglong; Chio, Floria H. N.; Oei, Tian P. S.; Leung, Freedom Y. K.; Liu, Xiangping (Frontiers in Psychology, 2017)
Interventions using the “Four Immeasurables Meditations” (FIM) are effective for various outcomes; however, whether increased meditation practice in these interventions leads to better results has not been well investigated. This systematic review included 22 FIM interventions that reported associations between the amount of meditation practice and its outcomes. Despite the heterogeneity in intervention components and outcome variables, there were generally few significant associations between amount of meditation practice and its outcomes. Specifically, only five studies reported that more than half of the calculated results were significant. In comparison with correlations between total amount of practice and overall outcomes, the short-term influence of meditation practice was evaluated in fewer studies; however, it had a better association with outcomes. More studies are required that address the underlying mechanisms that elucidate how meditation practice leads to outcome changes in daily life. In this study, two promising mechanisms with initial evidence were discussed. This review also summarized common methodological issues including a lack of experimental manipulation and inaccurate measuring of meditation practice.